Assessing the prevalence of generalized anxiety disorder in a multicultural medical education setting in Saudi Arabia during the COVID-19 pandemic - Ashraf, Nader; Arabi, Tarek Ziad; Dabaliz, Alhomam; Abou Shaar, Bader; Baqal, Omar Javed; Taha, Rand Mohammad; Baqal, Eman Javed; Alkodaymi, Mohamad Salim; Obeidat, Akef; Ouban, Abderrahman (Frontiers in Psychiatry, 2024)
Introduction: Mental health among medical students is an area that has been increasingly garnering world-wide attention. Yet, despite this increased attention, research related to anxiety disorders in Saudi Arabia remain limited. This study aims to address this gap by assessing the prevalence of generalized anxiety disorder (GAD) as well as explore its association with students' sociodemographic factors and academic performance among medical students in a Saudi Arabian institute that has a diverse, multicultural student body.Methods:Our study takes place in a unique educational environment: a privately funded institute in Riyadh, the capital of Saudi Arabia, with 32% of its student body comprising international students from over 40 countries, during the COVID-19 pandemic. Our study deploys the use of a survey that was sent to the students at this institute via their institutional emails. A survey containing 33 items assessing demographics, GAD using GAD-7 questionnaire, stress-relief measures, online learning experience during the pandemic, mental disorders, anxiety associated with the pandemic, two openended questions, and one item assessing sleep difficulty.Results:The results of the survey showed that a significant majority of the responders' scores in the GAD-7 assessment were in the range of moderate to severe anxiety. The results also suggest that low cGPA and the first academic years are significantly associated with higher GAD-7 scores. Students found severe time constraints, difficult educational content, and lack of psychological support to be major sources of stress. Furthermore, students suggested providing an in-house psychologist, personalized feedback, and guidance on study tactics as methods to reduce anxiety.Conclusion:These findings, among others, suggest a need for further studies and research in this field to uncover broader patterns and inform targeted mental health support strategies.